Validation of Self-Reported Anthropometrics in Female College Freshmen - LEONE, RYAN J. (Int J Exerc Sci, 2016)
Most investigations concerning the validity of self-reported anthropometrics focus on weight, height, and body mass index. This study extends those investigations by exploring the impact of self-reporting bias on the disease risk indicators of waist circumference and body fat percentage. Female college freshmen (n=128) self-reported weight and height, then underwent measurements for weight, height, waist circumference, and body fat percentage. Self-reporting bias was defined as self-reported minus directly-assessed anthropometric value. Despite no differences in self-reported versus directly-assessed weight or height for the total group, students with high waist circumference and excess fat under-reported their weight by 2.3±4.4 lb (p<0.05). Self-reporting bias was negatively correlated with waist circumference (r=−0.362; p<0.001) and body fat percentage (r=−0.317; p<0.001). Although many female college freshmen accurately represent their weight, those with excess fat and waist circumference under-reported their weight. This may lead to missed opportunities for risk identification, prevention, and intervention.